Bond behaviour of steel-reinforcing bars in Crumb Rubber Concrete (CRC). Issue 1 (2nd January 2020) - Li, Danda; Gravina, Rebecca; Zhuge, Yan; Mills, Julie E.
ABSTRACT: This paper assesses the bond-slip behaviour of Crumb Rubber Concrete (CRC) with embedded steel bars. A series of pull-out tests were conducted using CRC with 18% of the sand replaced by crumb rubber and traditional concrete (TC), with embedded steel bars of 12 mm and 16 mm in diameter. An ABAQUS model was developed to simulate the bond-slip relationship using cohesive elements and the model predictions agreed well with experimental results. The standardised bond strength of steel bars embedded in CRC is slightly lower than that of steel bars embedded in traditional concrete. The steel to concrete bond mechanism in CRC displayed similar behaviour to TC. Numerical results verified that the bond stress was uniform for short embedment bond specimens. A modified Eligehausen-Bertero-Popov model was able to satisfactorily predict the bond-slip relationship.